GE_GERICHTE P/5231/2025 vom 11. Dezember 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;PLAINTE PÉNALE;MÉNAGE COMMUN;VOIES DE FAIT;LÉSION CORPORELLE;INJURE;MENACE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL) | CPP.310; CP.31; CPP.304; CP.123; CP.126; CP.180; CP.177; CP.181